ACE awareness in school nursing – becoming a trauma-informed service. (2nd February 2022) - Parker, Caroline
Abstract : Adverse childhood experiences (ACEs) can have a serious impact on children and young people's mental health and wellbeing, as well as affect their future. Caroline Parker explains why ACE awareness is essential for school nurses and shares her experience of developing training.